Effect of the Electrolyte Temperature and the Current Density on a Layer Microhardness Generated by the Anodic Aluminium Oxidation - Emil Spišák; Miroslav Gombár; Ján Kmec; Alena Vagaská; Erika Fechová; Peter Michal; Ján Piteľ; Daniel Kučerka (Advances in Materials Science and Engineering)
The paper investigates the influence of the chemical composition and temperature of electrolyte, the oxidation time, voltage, and the current density on Vickers microhardness of aluminium oxide layers, at the same time. The layers were generated in the electrolytes with different concentrations of sulphuric and oxalic acids and surface current densities 1 A·dm−2, 3 A·dm−2, and 5 A·dm−2. The electrolyte temperature varied from −1.78°C to 45.78°C. The results have showed that while increasing the electrolyte temperature at the current density of 1 A·dm−2, the increase in the layer microhardness values is approximately by 66%. While simultaneously increasing the molar concentration of H2SO4 in the electrolyte, the growth rate of the microhardness value decreases. At the current density of 3 A·dm−2, by increasing the electrolyte temperature, a reduction in the microhardness of the generated layer occurs with the anodic oxidation time less than 25 min. The electrolyte temperature is not significant with the changing values of the layer microhardness at voltages less than 10.5 V.